(untitled) (International Journal of Applied Research in Management and Economics, 2021)
In a rapidly changing world, people need to create differences in order to participate in the labor market, and in the same way, for businesses to remain strong in the market. Especially due to the high uncertainties caused by the Covid-19 pandemic, it has become a must to update and possess the competencies that will make the difference at the individual and organizational level. This paper examined the competencies in the Covid-19 process, taking into account the history of competencies, their development over time and the types of competencies. In particular main aims of this paper are to suggest individual and organizational competencies that enable to exceed the average performance in the current pandemic conditions, to make contribution to ‘competencies and Covid-19’ literature, and to create a road map for the future managers and organizations. In this context, relevant literature was reviewed in detail and opinions were shared accordingly. As a result, cognitive and emotional attitudes of employees and managers are considered as individual competencies, whereas competencies related to agility, digitalization, human resources management, and teamwork are suggested as organizational ones. However, it would not be wrong to state that the two types of competencies are not completely separate from each other.